Modulación local de un canal operado por depósito - Montalvo, Gema B. (Revista Complutense de Ciencias Veterinarias, 2007)
In T lymphocytes, the Ca2+ entry mainly occurs through a particular type of store-operated Ca2+ (SOC) channel known as ICRAC. These channels open as consequence of Ca2+ stores emptying which is induced by inositol trisphosphate action next to recognition of an antigen. Local Ca2+ microdomains act as negative feedback regulators of CRAC channels promoting inactivation processes. Mitochondria by serving as intracellular Ca2+ buffers have been indicated to control the activity of ICRAC, however, the possibility of a factor released from mitochondria have been also pointed out, but no direct evidences have obtained at this respect yet. Thus, metabolically competent respiring mitochondria were able to reduce Ca2+-mediated inhibition of CRAC channels in the presence of high concentrations of different intracellular chelators and inhibitors of the endoplasmic reticulum Ca2+-ATPase. Recently, our group has shown that this effect is mainly mediated by a soluble mitochondrial factor (ATP) than can act as calcium chelator. In this context, we have begun to study other elements than could to exert a local control in the activity of CRAC channels as protein kinase C, plasma membrane calcium ATPase or the contribution of the lipidic composition of plasma membrane.